Kontroversi Produk Bank SharÃ®âah - Rokhim, Abdul (ISLAMICA: Jurnal Studi Keislaman, 2010)
This paper discusses the views of Muslims on the nature and legitimacy of bank interest as far as Syariâah law is concerned. Three views are presented here. First is the view of the neo-revivalists who argue that bank interest is legally illegitimate and that it is a form of riba. Second is the view ofâamong othersâFazlur Rahman who believes that bank interest is not riba. And third is the view that bank interest is in the state of legal doubtfulness (shubhat). We do not support particular view in this paper. But in principle it seems particularly legitimate to argue that Islam is a religion of social wellbeing in which any transaction should be free from such illegitimate practices as riba, gharar (cheating), and financial speculation. However, we also argue that bank interest is too complicated to be equated with riba. There are no accepted standards and qualifications by which the two can be said as the same. To this complex issue we dedicate our paper as a contribution to the issue at hand.